Types and appearance of equipment in architectural monuments - Gulmirzaev O’ktam (Research Parks Publishing LLC, 2022)
In this article we will restore, conserve, reconstruct, repair, restore all architectural and historical architectural monuments and archeological finds, and pass them on to the next generation in their entirety while preserving their artistic value